2010
DOI: 10.1007/s11096-010-9370-4
|View full text |Cite
|
Sign up to set email alerts
|

Potential drug–drug interactions and radiodiagnostic procedures: an in-hospital survey

Abstract: Among patients undergoing radiological examination, types and predictors of potential DDIs appeared in agreement with other kind of in-hospital populations. Premedication revealed to be a proxy predictor for potential DDIs. Considering the poor capability of the prescriber in recognizing interactions, their systematic evaluation (using an informatics tool) in patients undergoing radiological examination might be helpful in preventing the occurrence of clinically relevant DDIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…No statistically significant differences were found between men and women regarding DDIs, which is consistent with findings described in previous studies carried out in primary care settings [11], [29], [34] as well as investigations carried out in other settings [35], [36]. Age is another important variable to consider in relation to drug use.…”
Section: Discussionsupporting
confidence: 90%
“…No statistically significant differences were found between men and women regarding DDIs, which is consistent with findings described in previous studies carried out in primary care settings [11], [29], [34] as well as investigations carried out in other settings [35], [36]. Age is another important variable to consider in relation to drug use.…”
Section: Discussionsupporting
confidence: 90%
“…In the same country, the study of Aparasus et al (2007) showed that over 11% of patients experience symptoms associated with DI, which led to increase of health care costs. According to Lapi et al (2010), it is estimated that there are more than 100,000 combinations of drugs, which may be responsible for several adverse drug events. Hammes et al (2008) defined DI as a specific type of adverse event that occurs when the effects of a drug are altered by the presence of another.…”
Section: Introductionmentioning
confidence: 99%